Understanding the Practices and Challenges in Antimicrobial Susceptibility Testing: A Qualitative Study of Medical Laboratory Technicians in Saudi Arabia - Hadia Farhan Makmi Al-enizi; Amina Yousef Kandeel; Aref Awad Al-Shammari; Mohammed Shabbut Alshammari; Eidah Adehim Aldhafiry; Ghazoua Mohammad Alshammeri (International Journal of Medical Toxicology and Legal Medicine, 2024)
Antimicrobial susceptibility checking out (AST) is a crucial tool for steering antibiotic remedy decisions and tracking antimicrobial resistance. However, little is thought about the practices and challenges faced by medical laboratory technicians (MLTs) in acting AST in Saudi Arabia. This qualitative take a look at aimed to discover the experiences, practices, and demanding situations of MLTs in conducting AST in Saudi Arabian healthcare settings. Semi-structured interviews have been performed with 15 MLTs operating in diverse healthcare centers across the us of a. Thematic evaluation discovered four foremost themes: (1) modern practices in AST, (2) challenges in performing AST, (three) expert development and training desires, and (four) pointers for improving AST practices. Participants reported variability in AST techniques, limited sources and infrastructure, inadequate schooling opportunities, and conversation gaps with medical groups as primary challenges. Findings spotlight the need for standardized protocols, more suitable schooling applications, advanced infrastructure and resources allocation at institutional stage for AST laboratories as key techniques to tackle challenges confronted through MLTs. This observe offers valuable insights into optimizing AST practices and ultimately improving patient care through effective antibiotic stewardship in Saudi Arabia.